Объяснение:
пгпнзнщмн8мн8с7ен88нананузнз
1. а) х(а+с)—х(а+b) = х(а+с—а—b) = х(с—b);
б) y(2а + 3b) — y(3а — b) = у(2а + 3b — За + b) = y(4b-а);
в) 2(а + 2x) + (3а — х) = (2а + 4x + За — x) = (5а + Зx);
г) с2(3а — 7с) — с2(5а + Зс) = с2(3а — 7с — 5а — 3с) — с2(—2 а — 10с) =с2(2а + 10с);
2. а) у (а + с) + х(а + с) = (а + с) (у + x);
б) x(3а + с) — z(3а + с) = (За + с)(х — z);
в) x(2х + 3) — 3(2x + 3) = (2x + 3)(x — 3);
г) 2к(3к - 4) + (3k - 4) = (3k - 4)(2k + 1);
Объяснение:
пгпнзнщмн8мн8с7ен88нананузнз
Объяснение:
1. а) х(а+с)—х(а+b) = х(а+с—а—b) = х(с—b);
б) y(2а + 3b) — y(3а — b) = у(2а + 3b — За + b) = y(4b-а);
в) 2(а + 2x) + (3а — х) = (2а + 4x + За — x) = (5а + Зx);
г) с2(3а — 7с) — с2(5а + Зс) = с2(3а — 7с — 5а — 3с) — с2(—2 а — 10с) =с2(2а + 10с);
2. а) у (а + с) + х(а + с) = (а + с) (у + x);
б) x(3а + с) — z(3а + с) = (За + с)(х — z);
в) x(2х + 3) — 3(2x + 3) = (2x + 3)(x — 3);
г) 2к(3к - 4) + (3k - 4) = (3k - 4)(2k + 1);